Nuclear Receptors in Asthma: Empowering Classical Molecules Against a Contemporary Ailment - Tiwari, Drishti; Gupta, Pawan (Frontiers in Immunology, 2021)
The escalation in living standards and adoption of ‘Western lifestyle’ has an allied effect on the increased allergy and asthma burden in both developed and developing countries. Current scientific reports bespeak an association between allergic diseases and metabolic dysfunction; hinting towards the critical requirement of organised lifestyle and dietary habits. The ubiquitous nuclear receptors (NRs) translate metabolic stimuli into gene regulatory signals, integrating diet influences to overall developmental and physiological processes. As a consequence of such promising attributes, nuclear receptors have historically been at the cutting edge of pharmacy world. This review discusses the recent findings that feature the cardinal importance of nuclear receptors and how they can be instrumental in modulating current asthma pharmacology. Further, it highlights a possible future employment of therapy involving dietary supplements and synthetic ligands that would engage NRs and aid in eliminating both asthma and linked comorbidities. Therefore, uncovering new and evolving roles through analysis of genomic changes would represent a feasible approach in both prevention and alleviation of asthma.